Investment decision behaviour of the Malaysian retail investors and fund managers: A qualitative inquiry - Jaiyeoba, Haruna Babatunde; Adewale, Abideen Adeyemi; Haron, Razali; Che Ismail, Che Muhammad Hafiz (Emerald, 2017)
Purpose – This study investigates the Malaysian retail investors and fund managers’ investment decision behaviours. The study has offered important opportunity for understanding the investors’ experiences, how they understand the Malaysian economy, and their priorities for company selection. Other main aspects of this study are how investors mitigate the influence of emotions and psychological biases, and challenges faced during investment decisions.